Bulk immunoassays for analysis of extracellular vesicles. (3rd April 2017) - Coumans, Frank A. W.; Gool, Elmar L.; Nieuwland, Rienk
ABSTRACT: There is increasing clinical interest in extracellular vesicles (EV) for diagnostic and treatment purposes. This review provides an overview of bulk immunoassays to analyse EV. Western blot and enzyme-linked immunosorbent assay are still the two predominant bulk immunoassays. Recently, new assays have become available that can detect exposure to EV concentrations that are up to 10, 000-fold lower. This is advantageous for applications that detect rare EV. Other important parameters are the detectable concentration range, the required sample volume, whether simultaneous presence of different antigens on a single EV can be detected, size selectivity of each assay and practical considerations. In this review, we will explain the working principles of the traditional and novel assays together with their performance parameters. The most sensitive assays are micro-nuclear magnetic resonance, surface plasmon resonance, and time-resolved fluorescent immunoassay.